2010
DOI: 10.1111/j.1750-3841.2010.01636.x
|View full text |Cite
|
Sign up to set email alerts
|

Cassava Starch Coating and Citric Acid to Preserve Quality Parameters of Fresh‐Cut “Tommy Atkins” Mango

Abstract: Combination of citric acid dipping (5 g/L) and cassava starch coating (10 g/L), with and without glycerol (10 g/L), was studied to verify the effectiveness of these treatments to inhibit enzymatic browning, to reduce respiration rate, and to preserve quality parameters of "Tommy Atkins" fresh-cut mangoes during storage at 5 degrees C. Color characteristics (L and C), mechanical properties (stress at failure), weight loss, beta-carotene content, sensory acceptance, and microbial growth of fruits were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 23 publications
5
50
0
4
Order By: Relevance
“…Carvacrol treatment significantly reduced weight loss in the T2 group compared with the C1 group (3.73 %) and in the T1 group compared with the C1 group (3.78 %) on the last day of storage. Chiumarelli et al (2010) reported that fresh-cut mango with an edible coating of cassava starch presented a significant reduction of weight loss compared with the uncoated control group. According to Chiumarelli et al (2010), the use of hydrophilic coatings, such as starch, has limitations that are related to water vapor barrier properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carvacrol treatment significantly reduced weight loss in the T2 group compared with the C1 group (3.73 %) and in the T1 group compared with the C1 group (3.78 %) on the last day of storage. Chiumarelli et al (2010) reported that fresh-cut mango with an edible coating of cassava starch presented a significant reduction of weight loss compared with the uncoated control group. According to Chiumarelli et al (2010), the use of hydrophilic coatings, such as starch, has limitations that are related to water vapor barrier properties.…”
Section: Resultsmentioning
confidence: 99%
“…Chiumarelli et al (2010) reported that fresh-cut mango with an edible coating of cassava starch presented a significant reduction of weight loss compared with the uncoated control group. According to Chiumarelli et al (2010), the use of hydrophilic coatings, such as starch, has limitations that are related to water vapor barrier properties. The presence of carvacrol in the edible coating, because of its hydrophilic characteristics (Burt 2004), may help lessen water loss from vegetables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Witepsol is a synthetic wax usually not only used in the pharmaceutical industry as excipient but also approved for human consumption; Carnauba wax (also named Brazilian wax) is naturally extracted from the leaves of a particular palm tree known as Copernicia cerifera, a plant native to the northeast of Brazil. [9][10][11][12] The encapsulation of such polyphenols has afforded, in vitro, protection against the digestive harsh conditions and has improved bioavailability. 8 Oral administration of SLN is the most attractive route due to its unquestionable commercial potential, but it continues to be a major challenge.…”
mentioning
confidence: 99%
“…It was suggested that appropriate antioxidants could change the cellular redox potentials which would inhibit the oxidation of phenols and delay browning (Pizzocaro et al, 1993). In the same regard, citric acid can delay browning reactions of fresh-cut mangoes during storage (Chiumarelli et al, 2010). Citric acid reduced tissue browning through lowering pH of tissue or chelating to the copper moiety of PPO (Verma and Joshi, 2000).…”
Section: Effect Of Antioxidants On Callus Biomass Browning Intensitymentioning
confidence: 99%